You are on page 1of 2

) (

u n +1 = u n + r

u n +1 = q u n
q

un = up + (n - p) r

u n = u p qn - p

)(p n

)(p n

q n - p +1 - 1
u p + ... + u n = u p
u + un

q - 1 u p + ... + u n = ( n - p + 1) p

)( q 1
a b c

2b = a + c

b = a c

:
) ( u n

nI

un M
un m

( u n )nI "n I M

( u n )nI "n I m

( u n )nI

nI

) ( u n

:
) ( u n

nI

u n +1 u n
u n +1 u n
u n +1 = u n

) ( u n
"n I
nI
) ( u n
"n I
nI

) ( u n
"n I
nI

:
( u n )nI u p :
( u n )nI u n u p :
( u n )nI u n u p :
16

"n I
"n I

) (

n a: a * :
a>0

a<0

lim n a = +

lim n a = 0

n +

n +

) (

q n: q R :
q >1

q =1

-1 < q < 1

q -1

lim q n = +

lim q n = 1

lim q n = 0

) ( q

n +

n +

n +

vn u n w n

lim v n = l lim u n = l
n +
n
lim w n = l
n +

u n - l v n
lim u = l
lim v n = 0 n n

n +

u n vn

u n vn

lim u = +
lim v n = + n + n

n +

lim u = -
lim v n = - n + n

n +

) : u n +1 = f ( u n
) ( u n :

u 0 = a

) u n +1 = f ( u n
f I f ( I ) I a I

) ( u n l f ( x ) = x

17